# A family has two cars. The first car has a fuel efficiency of 40 miles per gallon of gas and the second has a fuel efficiency of 20 miles per gallon of gas. During one particular week, the two cars went a combined total of 2200 miles, for a total gas consumption of 75 gallons. How many gallons were consumed by each of the two cars that week?

The car that has a fuel efficiency of 40 mpg consumed 35 gallons, while the car that has a fuel efficiency of 20 mpg consumed 40 gallons.

Step-by-step explanation:

The variable a will represent the fuel consumed by the first car, and the variable b will represent the fuel consumed by the second car.

Set up the formula: a+b=75, which will represent the total gas consumption.

The formula 20a+40b=2200 will help you solve.

To solve, we will first solve for a by changing the formula from a+b=75 to b=75-a. Then you plug in the value of b to the second formula:

20a+40(75-a)=2200

20a+3000-40a=2200

3000-20a=2200

After subtracting 3000 from both sides, you are left with -20a=-800. Multiply both sides by -1 so that both sides are positive:

20a=800

a=40

Now that we know that the car with a 20 mpg fuel efficiency consumed 40 gallons that week, we can subtract 40 from 75, leaving us with 35 being the amount of gallons consumed by the car with a 40 mpg efficiency.

## Related Questions

What is the measure angle of 3 ?
The measure angle of 4?

Angle 4=83
Angle 3=46

Explanation:
For angle 4- Angles in a triangle add to 180 degrees
46+51=97 180-97=83
For angle 3- angles on a straight line add to 180 degrees
51+83=134 180-134=46

I hope this helped :)

Kellen bought a souvenir cup at the zoo for \$7.50. Any time Kellen bringsthe
cup back to the zoo, he can purchase fountain drinks for \$0.75 each. If
Kellen has spent \$12.75 so far, including the original purchase of the cup,
how many fountain drinks has he purchased?

7 fountain drinks

Step-by-step explanation:

\$12.75-\$7.50=\$5.25

\$5.25/\$0.75=7

Please, need this urgently.Graph the function f(x) = 18(0.8)x.

an exponential graph decreasing from the left and crossing the y axis at 0 comma 21
an exponential graph decreasing from the left and crossing the y axis at 0 comma 5
an exponential graph decreasing from the left and crossing the y axis at 0 comma 18
an exponential graph decreasing from the left and crossing the y axis at 0 comma 8

i think the answer is:

D - an exponential graph decreasing from the left and crossing the y axis at 0 comma 8

the answer is D

Step-by-step explanation:

i took the test

Which number is located between 1.2 and 1.4 on the number line

1.3

Step-by-step explanation:

a number between 2 and 4 is 3

Step-by-step explanation:

Can Someone please explain how to solve this. The directions say, "Solve the system by graphing. Then check your solution."​

Try this suggested solution (see the attached picture, the answer is [-2;1]).

1 step to drow the graph required in the condition;

2 step to find intersection point (this is the A point);

3 step, check stage, to solve the system of two equations.

4 to compare the results in step 2 and step 3.

If f(x)=2x-3 find the following
f(7)=
f(-2)=
f(-4)=

The value of f(7) ,f(-2) and f(-4) will be 11 , -17 and -31 respectively.

### What is a function?

A certain kind of relationship called a function binds inputs to essentially one output.

A function can be regarded as a computer, which is helpful.

The machine will only accept specified inputs, described as the function's domain, and will potentially produce one output for each input.

In other words, the function is a relationship between variables, and the nature of the relationship defines the function for example y = sinx and y = x +6 like that.

Given,

f(x)=2x-3

f(7) so put x = 7

f(7) = 2(7) - 3

f(7) = 11

Now,

f(-2) so put x = -2

f(-2) = -2×7-3

f(-2) = -17

Now,

f(-4) so put x = -4

f(-4)= -4×7-3

f(-4) = -31

Hence,The value of f(7) ,f(-2) and f(-4) will be 11 , -17 and -31 respectively.

For more about the function,

brainly.com/question/23712366

#SPJ2

Step-by-step explanation:

f(x)=2x-3

now,

f(7)=2× 7-3

=14-3

=11

f(-2)='-2×7-3

= -14-3

b= -17

f(-4)= -4×7-3

= -28-3

= -31